EKSISTENSI LEMBAGA KEUANGAN MIKRO DAN DAMPAKNYA TERHADAP SOSIAL EKONOMI MASYARAKAT KABUPATEN BENGKALIS - Mujiono Mujiono (Politeknik Negeri Bengkalis, 2016)
Abstract: The existence of microfinance institutions in rural areas plays strategic roles to boost the community socioeconomic development. Microfinance Institution of Rural Economic Enterprises- Savings and Loans (LKM UED-SP) of Bengkalis Regency, until 2016, has been able to develop both cumulative and current year loans volume. The development has also occurred on the poor household loans which continuously increasing every year. The numbers of debtors according to genders have shown a positive development. The average of male debtors were 28,283 people with the ratio average of 66.20% , female debtors were 14, 517 people with the ratio average of 33.80%. In addition, 538 of the debtors were from poor families with the ratio average of 1.28%. Among the business sectors, the debtors including several sectors such as trading, agriculture, plantation, fishery, animal husbandry, small industries and services: with the highest sectors nominated by plantation of 51.96%, trading of 30.77% and service sector of 6.28% - while the other sectors were below 5%. The government capital ratio was in average of 93.72% and from the current year profit of 6.28%. The number of female staff developed in average of 204 people each year. The development on productive business loans was in average of 57.72% and poor household loans of about 32.79%. The staff’s productivity was about 105 people per staff with the average loan volume of Rp. 1.344.881.683,-. The average of staff’s incentive reached Rp. 1.173.720.029,- with the ratio of Rp. 2.558.789,- per staff. Keywords: Micro Finance and Social Performance